Higher baseline serum bilirubin levels are associated with increased risk of early neurological deterioration in women with acute ischemic stroke - Sun, Meng; Weng, Yingfeng; Cheng, Jiwei; Li, Guoyi; Xiao, Qian (Frontiers in Neurology, 2024)
Background and objectives: Early neurological deterioration (END) occurs in up to one-third of patients with acute ischemic stroke (AIS) and associated with poor outcome. This study aims to investigate the association of total bilirubin (TBIL), direct bilirubin (DBIL) and indirect bilirubin (IBIL) with END in different genders. Methods: This study was a cross-sectional retrospective study with 344 AIS patients enrolled. We retrospectively reviewed consecutive AIS patients with END through a medical record retrieval system and enrolled patients as control randomly from the AIS patients without END at the same period. The bilirubin levels were compared between the END group and No END group. The correlations of bilirubin with END were assessed according to the bilirubin tertiles on the cohort of different genders. Results: In women, as the bilirubin level increased, the occurrence of END showed an increasing trend. The linear association was significant based on the tertiles of all bilirubin types (TBIL p = 0.003; DBIL p = 0.025; IBIL p = 0.025), while in men no similar trend was observed. After adjustment for confounders, higher TBIL (p for trend 0.009) and DBIL (p for trend 0.033) levels were associated with increased risk of END in women. The adjusted OR for T3 relative to T1 was 5.240 (95% CI 1.496-18.347) in TBIL and 3.549 (95% CI 1.089-11.566) in DBIL. Multivariate logistic regression showed that DBIL was independently associated with END in women (OR 1.717, 95% CI 1.106-2.666). The study also found that DBIL was superior to TBIL and IBIL in prediction of END occurrence in women, with greater predictive value. Discussion: There were gender differences in the relationship between bilirubin and END, and DBIL level was positively associated with END occurrence in women, not in men. DBIL had greater incremental predictive value for END than TBIL and IBIL.